Catchment Area in Health Services: Studies in Kasembon and Pujon Subdistricts, Malang Regency - Deasy Ariffiani; Sri Umiyati; Sri Wahyuni (Jurnal Administrasi Publik (Public Administration Journal), 2022)
This study aims to analyze the application of health services in Kasembon and Pujon Districts in Malang Regency based on the catchment area perspective, as well as analyze the challenges of the practice of accessing health services. With the background of service improvement efforts that have been done a lot, but in fact, the accessibility is very difficult or even impossible to change. This study uses a qualitative method with a soft system methodology (SSM) approach. The data processing of the findings is carried out through a comparison of real facts with alternative normative models so that they have the opportunity to generate improvement ideas. The results of the study show that there are still challenges in the form of weak access to health insurance, facilities, and human resources, quality standards of health services, the role of monitoring stakeholders, to patterns of community participation. This then resulted in 3 main points of concern to produce corrective action, namely the evaluation of the health care system, health service practice standards, and the accuracy of the health service program targets. This study recommends a top-down mechanism priority by optimizing the improvement of the quality of health service standards in Kasembon and Pujon by policymakers and bottom-up through a participatory pattern by optimizing local public service agencies (BLUD) through community synergy with various institutions and government at lower levels. for managing access to health services.